Littoral 2010 – Adapting to Global Change at the Coast: Leadership, Innovation, and Investment 2011
DOI: 10.1051/litt/201111003
|View full text |Cite
|
Sign up to set email alerts
|

MISEEVA : Set up of a transdisciplinary approach to assess vulnerability of the coastal zone to marine inundation at regional and local scale, within a global change context

Abstract: MISEEVA (2008MISEEVA ( -2011 aims to assess coastal zone vulnerability to marine inundation by integrating the physical and socio-economical aspects at different temporal (2010, 2030 and 2100) and spatial (local to regional) scales. The Languedoc Roussillon (France) region was chosen as a pilot site, focusing on local sites from Villeneuve-lès-Maguelone to Carnon, in Hérault.It required the development of a transdisciplinary methodology to enable transfers of knowledge and promote interdisciplinary iteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
(6 reference statements)
0
11
0
1
Order By: Relevance
“…The area has been affected by several severe storms in the recent past De La Torre et al, 2013). In particular, the 1982 storm caused flooding and damages in the place of interest (Vinchon et al, 2011b).…”
Section: Coastal Sitementioning
confidence: 99%
See 1 more Smart Citation
“…The area has been affected by several severe storms in the recent past De La Torre et al, 2013). In particular, the 1982 storm caused flooding and damages in the place of interest (Vinchon et al, 2011b).…”
Section: Coastal Sitementioning
confidence: 99%
“…If high resolution topo-bathymetric data such as LiDAR are available, such approach can be valid for the present situation. Such a study has been actually undertaken to evaluate marine flooding under several sea-level rise scenarios on our test site (Vinchon et al, 2011b). If we incorporate this study in the background knowledge (Table 2), this will lead to reduced uncertainties during the first years of simulations.…”
Section: Defining Research Priorities Based On the Global Sensitivitymentioning
confidence: 99%
“…2). A regional study (Vinchon et al, 2008) identified that the lido is a regional "hot-spot". DEMO is characterised by significant touristic activities.…”
Section: Study Site and Hazard Thresholdmentioning
confidence: 99%
“…Secondly, to identify the minimum acceptable return period (T RC ) of such a flood, we focus on individual acceptability. For this purpose, some results on individual perception from the national research project MISEEVA (Vinchon et al, 2010) are used. Within surveys, the following question has been asked to inhabitants and merchants of DEMO city: "Above which frequency of sea flooding inundation of your house, would you leave your home?".…”
Section: Study Site and Hazard Thresholdmentioning
confidence: 99%
“…The effects of winter storms are expected to be exacerbated by climate change‐related SLR, and although sea‐level estimates for 2030 do not exceed 0.07 m, they vary between 0.35 and 1 m for 2100 (Vinchon et al ; Lurton et al ).…”
Section: French Coastline Planning Is Maladapted To the Effects Of Exmentioning
confidence: 99%